2005
DOI: 10.1007/s11258-004-2486-7
|View full text |Cite
|
Sign up to set email alerts
|

Fine-scale spatial variation in plant species richness and its relationship to environmental conditions in coastal marshlands

Abstract: Previous studies have shown that variations in environmental conditions play a major role in explaining variations in plant species richness at community and landscape scales. In this study, we considered the degree to which fine-scale spatial variations in richness could be related to fine-scale variations in abiotic and biotic factors. To examine spatial variation in richness, grids of 1 m 2 plots were laid out at five sites within a coastal riverine wetland landscape. At each site, a 5 · 7 array of plots wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
(58 reference statements)
0
9
1
Order By: Relevance
“…The lack of biomass effects in this study contrasts with other SEM analyses that found significant relationships between standing aboveground biomass or cover and species richness (Grace and Pugesek 1997, Gough and Grace 1999, Grace and Guntenspergen 1999, Grace and Jutila 1999, Grace et al 2000, Weiher et al 2004, Mancera et al 2005, Grace and Keeley 2006, but in those studies live shoot biomass and litter were not considered separately. Finally, I found that initial species richness and evenness remained important, indicating that, similar to other studies (Grace and Guntenspergen 1999), plot history is an important determinant of current community structure.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The lack of biomass effects in this study contrasts with other SEM analyses that found significant relationships between standing aboveground biomass or cover and species richness (Grace and Pugesek 1997, Gough and Grace 1999, Grace and Guntenspergen 1999, Grace and Jutila 1999, Grace et al 2000, Weiher et al 2004, Mancera et al 2005, Grace and Keeley 2006, but in those studies live shoot biomass and litter were not considered separately. Finally, I found that initial species richness and evenness remained important, indicating that, similar to other studies (Grace and Guntenspergen 1999), plot history is an important determinant of current community structure.…”
Section: Discussioncontrasting
confidence: 99%
“…A number of recent studies have taken a holistic approach to examine the controls on plant diversity in a range of communities including coastal wetlands, grasslands, and shrublands (Grace and Pugesek 1997, Gough and Grace 1999, Grace and Guntenspergen 1999, Grace and Jutila 1999, Grace et al 2000, Weiher et al 2004, Mancera et al 2005, Grace and Keeley 2006. These studies used structural equation modeling (SEM) to explicitly evaluate the causal relationships among multiple interacting variables that together affect diversity (Shipley 2000, Grace 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Midwestern U.S. fens as small as 80 ha can have .500 species (Amon et al 2002). Freshwater coastal marshes in Louisiana average 8-12 species per m 2 (Mancera et al 2005), and transects of temperate to subtropical North American wetland vegetation that are hundreds to thousands of meters long commonly record 50-200 species (e.g., Laliberte et al 2007, Flinn et al 2008, Peirson and Evans 2008, Carr et al 2009). The high diversity of BCR relative to other fossil assemblages probably reflects unusual preservation of herbaceous as well as the few woody plants, rather than high diversity of the original flora compared with extant floras in similar habitats.…”
Section: Discussionmentioning
confidence: 99%
“…The direct and indirect effects of abiotic and biotic variables – for example, canopy cover and mineral content of soil (Weiher et al. , 2004), fine‐scale spatial variations in plant species richness (Mancera et al. , 2005), or time since the last fire (Laughlin & Grace, 2006) – have been reported from various natural systems.…”
Section: Introductionmentioning
confidence: 99%
“…Failure to distinguish these different paths and to assign them the correct importance could lead biologists to examine spurious relationships (Shipley, 2000). The direct and indirect effects of abiotic and biotic variables -for example, canopy cover and mineral content of soil (Weiher et al, 2004), fine-scale spatial variations in plant species richness (Mancera et al, 2005), or time since the last fire (Laughlin & Grace, 2006) -have been reported from various natural systems. Ideally, the effects of these interrelated variables should be tested experimentally, but in many cases manipulations are not possible because of the high number of factors involved.…”
mentioning
confidence: 99%